Anglicization of Written Igbo Personal and Place Names: A Sociolinguistic Study - Nnamdi-Eruchalu, Geraldine Ifesinachi (Advances in Social Sciences Research Journal, 2021)
The Igbo people are at the verge of losing their language, culture and identity to the English Language [Azuonye 2002, Asonye 2013, Emeka-Nwobia 2020]. This work aims at investigating into the Anglicization of written Igbo personal and place names with a view to highlighting the extent of spellings and pronunciation inconsistencies, discover what impact it has on the learning and development of the language, and discover ways the attitude of the people can be changed towards the language to forestall its death. It argues that the spelling inconsistencies it introduced to the language is a source of challenge to learners, the majority of whom already have negative attitude towards the language. Ogbalu [1974], Oruchalu [1979] and Okodo [2008] made lists of anglicized names with their correct Igbo spellings, and decried the practice. The data for this research were collected from personal experiences, class lists, radio and television programmes, the internet, social and print media, and interviews. It concludes that a change in the attitude of the people towards their language, culture and identity as well as total implementation of the Onwu Orthography with regards to the spelling of personal and place names will complement the efforts being made to sustain the language.